(untitled) (Social Science Review, 2025)
This paper attempts to understand how religion plays a pivotal role in politics with a focus on the process through which amalgamation of religion and politics usually takes place, and how such amalgamation impacts the political sphere in Bangladesh. By using Riaz’s political expediency theory, this paper argues that the political use of religion was institutionalized by the military regimes to consolidate their power base and while for democratic governments, the primary reason to use religion as a political agenda was to gain mass popularity. However, this tendency always possesses the risk of falling out of balance and creating communal tension. The purpose led to materializing drastic steps such as state- sponsored patronization, constitutional modification, depiction of religious attitudes by political leaders, political expediency, and application of digital platforms for political purpose, that eventually caused the amalgamation of religion and politics. The impact of such amalgamation is found primarily negative, including restricting attitude toward liberal ideology and threat to minorities. Social Science Review, Vol. 41(1), June 2024, Page 39-56.